A Comment on "Improving Women's Mental Health During a Pandemic" - Abel Brodeur; Lenka Fiala; Jack Fitzgerald; Essi Kujansuu; David Valenta; Ole Rogeberg; Gunther Bensch (Institute for Replication (I4R), 2025)
Vlassopoulos et al. (2024) find that after providing two hours of telephone counseling over three months, a sample of Bangladeshi women saw significant reductions in stress and depression after ten months. We find three anomalies. First, estimates are almost entirely driven by reverse-scored survey items, which are handled inconsistently both in the code and in the field. Second, participants in this experiment are reused from multiple prior experiments conducted by the paper's authors, and estimates are extremely sensitive to the experiment from which participants originate. Finally, inconsistencies and irregularities in raw survey files raise doubts about the data.
https://osf.io/pvkhy/
Keywords: B41; C12; I12; I18; J16; O12; 330; Reproduction; Replication; Mental health; COVID-19 pandemic